1997
DOI: 10.5144/0256-4947.1997.601
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Hepatitis C Virus Isolates from Saudi Patients by Analysis of Sequences from PCR-Amplified Core Region of the Virus Genome

Abstract: We investigated the genotype distribution of hepatitis C virus (HCV) among Saudi patients with chronic hepatitis C. Serum specimens from 119 native Saudi Arabian patients with chronic hepatitis C, as documented by serology and polymerase chain reaction (PCR) for HCV RNA, were used. Genotyping was performed by reverse transcription-PCR, using specific primers at the core region of HCV genome, and DNA sequencing of the resultant amplicons. It was found that the majority of samples (47.9%) belong to genotype 4, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The subtypes found in Iran, were neither similar to those in neighbouring countries like Turkey or Pakistan, where the dominating subtypes are 1b and 3 [Abacioglu et al, 1995;Shah et al, 1997] nor to those in Middle East countries such as Iraq, Saudi Arabia, Yemen, Kuwait where 4 is the most prevalent HCV genotype [Ohno et al, 1996;Al-Ahdal et al, 1997;Chamberlain et al, 1997;Fakeeh and Zaki, 1999]. The similarities in the distribution of the HCV subtypes in Iran with European countries and the USA might support a common origin through large-scale medical contacts between Iran and these countries.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The subtypes found in Iran, were neither similar to those in neighbouring countries like Turkey or Pakistan, where the dominating subtypes are 1b and 3 [Abacioglu et al, 1995;Shah et al, 1997] nor to those in Middle East countries such as Iraq, Saudi Arabia, Yemen, Kuwait where 4 is the most prevalent HCV genotype [Ohno et al, 1996;Al-Ahdal et al, 1997;Chamberlain et al, 1997;Fakeeh and Zaki, 1999]. The similarities in the distribution of the HCV subtypes in Iran with European countries and the USA might support a common origin through large-scale medical contacts between Iran and these countries.…”
Section: Discussionmentioning
confidence: 87%
“…These strains might have been introduced from one of the neighbouring Arabic countries, where genotype 4 is prevalent [Al-Ahdal et al, 1997;Chamberlain et al, 1997;Fakeeh and Zaki, 1999] and become spread at dialysis units. Imports of foreign HCV strains from other countries have been documented from South Africa [Smuts and Kannemeyer, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…3,17 Only one study in the Kingdom found genotype 3a in two (1.6%) of 119 patients with chronic hepatitis infection. 9 We did not find genotypes 3 and 6 in any of our patients in the Western Province.…”
mentioning
confidence: 85%
“…The few published studies have been carried out mainly in institutions in the Riyadh area. [6][7][8][9][10][11][12] The purpose of our study was to determine the prevalent HCV genotypes among HCV seropositive Saudi patients in the Western Province, and to study the relationship between types/subtypes, clinical status and liver histology.…”
mentioning
confidence: 99%
“…However, several recent studies carried out in Europe have indicated changes in genotype distribution and have underlined the increasing prevalence of HCV-4 1315. The prevalence of HCV antibody positivity in Saudi Arabia ranges from 1% to 3%,1617 with genotype 4 representing 60% to 70% of these infections 1821. There are limited reports on the treatment of chronic HCV-4 patients from the Middle East (mainly from Saudi Arabia, Egypt, Kuwait, and Qatar),2231 or elsewhere 3235.…”
mentioning
confidence: 99%